Breast tuberculosis: a case report - Hind Bouyabla; Ibtissam Bellajdel; Fatima Zahra Bouabdellaoui; Samia Malki; Amal Bennani; Hafsa Taheri; Hanane Saadi; Ahmed Mimouni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Mammary tuberculosis is a rare disease that affects young women during the genital period, usually between the ages of 20 and 40 years, and remains rare in postmenopausal women. Its risk factors are multiparity, breastfeeding, breast trauma and chronic mastitis. Depending on the mode of contamination, there are 2 forms of mammary tuberculosis: primary or secondary. On ultrasound, breast tuberculosis often appears as a heterogeneous hypoechoic image, poorly limited with minimal posterior enhancement. It may also appear as a hypoechoic, homogeneous or heterogeneous image, well limited with posterior enhancement and some calcifications. Histological criteria suggestive of breast tuberculosis are the presence of epithelioid follicles and Langhans-type giant cells, which may or may not be associated with caseous necrosis. A certain number of diagnoses must be eliminated before the diagnosis of breast tuberculosis can be made, in particular breast cancer; it should be noted that the literature describes forms associating cancer and breast tuberculosis, hence the need for a histological study of the breast tissue in order to eliminate an associated carcinoma. It poses diagnostic and therapeutic problems. Current treatment is based on antituberculosis chemotherapy sometimes associated with surgery. The evolution of the disease is usually favourable with a well conducted treatment.